2018
DOI: 10.1021/acs.langmuir.8b02385
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Molecular Interactions in Glycerol Adsorption at the Metal–Water Interface with Density Functional Theory

Abstract: Glycerol is an extremely versatile platform molecule for chemical and fuel production, as evidenced by successful demonstrations in electrochemical and thermochemical processes, where key catalytic chemistries occur at the solid–liquid interface. Despite the remarkable progress made in enriching the first-principles-based computational tool set to reveal and characterize solvent structures in the past decade, techniques for realistic and efficient molecular-level modeling to study aqueous-phase glycerol chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…77,218 Different theoretical approaches such as density functional theory (DFT) have been developed to examine the oxidation of C2-C3 alcohols, namely ethanol, [219][220][221][222] ethylene glycol 223 and glycerol. 35,176,[224][225][226][227][228][229][230][231] For the electrocatalysis community, the most extracted information is more valuable when a direct correction is made between DFT data wherein the Fermi level potential is commonly expressed in "eV" and those of the electrode/electrical potential traditionally articulated as "V vs SHE" or in the best case as "V vs RHE" (RHE being the universal electrochemical reference that does not depend on the pH of the electrolytes). The relationships of the potential E between the "vacuum scale" and "electrochemical scale" are given below by Eqs.…”
Section: Theoretical and Computational Insights In C2 And C3 Alcohols Oxidationmentioning
confidence: 99%
“…77,218 Different theoretical approaches such as density functional theory (DFT) have been developed to examine the oxidation of C2-C3 alcohols, namely ethanol, [219][220][221][222] ethylene glycol 223 and glycerol. 35,176,[224][225][226][227][228][229][230][231] For the electrocatalysis community, the most extracted information is more valuable when a direct correction is made between DFT data wherein the Fermi level potential is commonly expressed in "eV" and those of the electrode/electrical potential traditionally articulated as "V vs SHE" or in the best case as "V vs RHE" (RHE being the universal electrochemical reference that does not depend on the pH of the electrolytes). The relationships of the potential E between the "vacuum scale" and "electrochemical scale" are given below by Eqs.…”
Section: Theoretical and Computational Insights In C2 And C3 Alcohols Oxidationmentioning
confidence: 99%
“…A few relationships applicable in the condensed phase have been reported. For example, Liu et al studied effects of water on adsorption energies of glycerol on Pd(111) facet 40 . They considered energies of individual interactions such as water–water, water‐Pd, and water‐glycerol in an additive fashion; adsorption energies of glycerol derivatives were estimated by counting the corresponding number of each type of bond formed by adsorbates.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Given the diverse possible orientation and adsorption modes of complex organic molecules, computational studies have been used to probe insight into interfacial phenomena. 31,32 Notably, for glycerol adsorption, calculated binding energies of reactant-surface molecular interactions revealed that C-H scissions, rather than O-H, gave rise to relatively more stable adsorbates, suggesting that first dehydrogenation step proceeded primarily at C atoms. 33 Besides, the stability of an adsorbate is inherently structure dependant as identified by other researchers.…”
Section: Initial Binding Modesmentioning
confidence: 99%